حد السرقة وأثره في الردع عن الجريمة - عصماني, عبد النور; دحدة, العربي; قطوطة, سليمان (University of Eloued-جامعة الوادي, 2018)
قام البحث بدراسة حد السرقة وأثره في ردع الجريمة، وقد قسم إلى مبحثين : المبحث الأول قد خصص لماهية السرقة وصفة حدها وشروط السرقة الموجبة للحد حيث عرجنا على تعريف السرقة وحكمها وفصلنا في صفتها و شروطها اما فيما يختص بالمبحث الثاني فقد تناولنا فيه عن إثبات السرقة وتكرا رها وما يسقط الحدThis research has studied the delimit of Stealing and its trace in deterring the crime, and it has been divided into to Methods :The first one was specified in knowing stealing and its delimited characteristics plus the duty conditions of Stealing . We also had shed the light on defining Stealing and its verdict and we have explained more about its characteristics and conditions so the second Method talked about the fact of Stealing and its repetition and what falls its limits after its duty . At end we had mentioned the most important outcomes . بعد وجوا أما في آخر البحث فقد ذيلناه بخاتمة تذكرنا فيها بأهم النتائج
مذكرة ماستر
Keywords: حد السرقة /الردع عن الجريمة; Limiter le vol/dissuader la criminalité